Chapter 3 Tourism arrivals and road victims: evidence from mediterranean regions (2019)
Despite the greater traffic congestion on roads, during peak season, most tourists in Mediterranean countries still choose to drive since that gives them greater flexibility in scheduling leisure or destination visiting. In addition, modern cars have become more comfortable, reliable, and safer with power steering, four-wheel drive, improved tires, air conditioning, cell phones, and advanced audio equipment. Yet, tourist driving is a risky activity. There are many uncertainties in tourist driving: the time taken on a tourist trip, the speed achieved on the trip, the chance of crashing, and the occurrence of a traffic accident, are all uncertain. A tourist in the role of driver will typically care about all of these possible outcomes. In addition, drivers tolerate various levels of risk and perception of risk has been shown to influence driving behavior Some features of a risk-loving driver include: drowsy driving (the dangerous combination of driving and sleepiness or fatigue), illegal parking, and driving under the influence of alcohol, narcotics or other impairments. If drivers in tourist destinations are risk averse, their utility of a certain outcome is greater than their utility of an expected value equal to the certain outcome. They will avoid the possibility of paying parking fines and avoid the hazard of motor vehicle collisions by adopting defensive-driving techniques. Risk-averse drivers’ actions can keep travellers safe on the road more than those of risk-loving drivers. When a tourist, as an economic agent, decides to drive to a tourist destination during high-season months, he takes into account the extra time it will take because of congestion on the roads at those times. Naturally, the slowing down of traffic is caused by risk-averse people on the road. Even the risk-loving driver becomes occasionally risk-averse on some occasions. However, a risk-averse driver generally does not take into account the effects of his driving on the congestion faced by others. This increase in the congestion he causes others is a negative externality. Adding up all these small externalities over thousands of personal vehicles totals a large aggregate externality. This translates to a large increase in paying attention to traffic by risk-averse drivers, which luckily, results in fewer accidents on the road.